2015
DOI: 10.1371/journal.pone.0141475
|View full text |Cite|
|
Sign up to set email alerts
|

Piscine Reovirus: Genomic and Molecular Phylogenetic Analysis from Farmed and Wild Salmonids Collected on the Canada/US Pacific Coast

Abstract: Piscine reovirus (PRV) is a double stranded non-enveloped RNA virus detected in farmed and wild salmonids. This study examined the phylogenetic relationships among different PRV sequence types present in samples from salmonids in Western Canada and the US, including Alaska (US), British Columbia (Canada) and Washington State (US). Tissues testing positive for PRV were partially sequenced for segment S1, producing 71 sequences that grouped into 10 unique sequence types. Sequence analysis revealed no identifiabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(86 citation statements)
references
References 27 publications
2
84
0
Order By: Relevance
“…One potential explanation for this disparity may involve genetic variation between PRV isolates. Siah et al [3] recently conducted a phylogenetic analysis of all segments of the PRV obtained from western North America as well as selected Norwegian and Chilean PRV genomes. With the exception of segment S4, samples of North American PRV clustered separately from the Norwegian and Chilean samples indicating that there are genetic differences across the genome between Pacific, Norwegian and Chilean forms of PRV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One potential explanation for this disparity may involve genetic variation between PRV isolates. Siah et al [3] recently conducted a phylogenetic analysis of all segments of the PRV obtained from western North America as well as selected Norwegian and Chilean PRV genomes. With the exception of segment S4, samples of North American PRV clustered separately from the Norwegian and Chilean samples indicating that there are genetic differences across the genome between Pacific, Norwegian and Chilean forms of PRV.…”
Section: Discussionmentioning
confidence: 99%
“…The dsRNA-binding activity of the MRV ơ3 protein inhibits the induction of type-1 IFN and activation of protein kinase R ( PKR ) which through its interaction with translation initiation factor ( eIF2α ) inhibits cellular mRNA translation, thereby, limiting viral protein production. Siah et al [3] compared the predicted structure of the North American PRV ơ3 protein to predicted ơ3 proteins based on Norwegian/Chilean sequences. These authors identified an amino acid difference which results in a predicted change in secondary structure from an “alpha-helix” in Norwegian/Chilean PRV source to a “sheet structure” in North American PRV sequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…trutta L.) [1820] implies that PRV infection not only occurs in Atlantic salmon but also in other salmonid fish species. HSMI-like diseases caused by PRV-related viral infections have also been reported in rainbow trout in Norway [21].…”
Section: Introductionmentioning
confidence: 99%